Hierarchical fault tolerance in wireless networked control systems - Makled, Esraa Aziz (AUC Knowledge Fountain, 2015)
Wireless Networked Control Systems (WNCS) have recently emerged as a replacement for wired control networks. Wireless networked control systems are more suitable for environments that require higher flexibility and robustness. In previous literature a wireless manufacturing line was proposed. The work-cells communication was through IEEE 802.11 technologies and a switched Ethernet backbone. This thesis is aiming to improve the current solution by adding a supervisor to the existing system. The supervisor could be either in passive or active mode. Passive supervisor would intervene when all controllers in the network fail, while active supervisor would act once any controller on the line fail. The system was simulated using OPNET software with 95% confidence analysis. The ability of the system to withstand external interference was assessed through adding a single band jammer to the OPNET simulation. The system was able to hold up to 8KB interfering file sent from a single band jammer affecting the full Wi-Fi spectrum. All results were subjected to a 95% confidence analysis The performability of passive and active supervisor systems was compared. A Markov model of both systems was built. It was shown that by time, the performability of a passive supervisor system is enhanced while that of an active supervisor system degraded. However, the active supervisor showed a better performability in all cases.